Las comisiones de la violencia más allá de la narrativa: Una posibilidad para la memoria histórica y las políticas de la memoria en la superación del conflicto - Jessica Santamaría González (Cambios y Permanencias, 2017)
The article analyzes what is the pertinence of studying the violence commissions elaborated in Colombia since 1958; It has to be understood thatbeyond a narrative paper, these commissions are fundamental part forstudying the construction of historical memoryin light of not only all the politics that involves the concept of memory but also the pertinence of the past as a chance in present times. Therefore it will be possible to understand this past like a timethat just had happened and thus a future in the Colombian land may be also a remarkable one for its inhabitants.